People's skills - Hawley, Casey Fitts (Idiot's guides., 2014)
This guide offers advice on the foundations of effective communication, tips on understanding and maximizing nonverbal communication, ways to handle conflict and difficult conversations, pointers on being more influential and persuasive, and a primer for public speaking to small or large groups.